Problemy proceduralne udostępniania informacji publicznej z punktu widzenia samorządu terytorialnego - Szczepaniak, Sylwester (Kwartalnik Prawa Publicznego, 2012)
The author discusses problems related to public information access procedure in those public entities which are obliged to provide public information. The main disadvantage of this regulation is its vagueness. In the literature the ‘citizen perspective’ approach is dominant, what significantly affects the purpose of the bill. Unfortunately, a comprehensive analysis of the bill indicate significant practical difficulties. Most of these problems are related the narrow approach of the regulation, and to the lack of connections with administrative law system, particularly, administrative procedures. The new regulation from September 2011, introducing the EU directive 2003/98/EC from 17th November 2003 about the re-use of public sector information, has not changed rules and procedures regarding public information access, and additionally it has not eliminated all legal doubts.